POLA PERENCANAAN PEMBAGIAN AIR SECARA EFISIEN PADA JARINGAN IRIGASI SETUPATOK - , Tanti Tri Putranti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Setupatok Reservoir is a surface water source used for irrigation activity. It is located in Sub-District Mundu, the Regency of Cirebon, the Province of Jawa Barat and covered 1.408 ha service area. Currently, it is failing to fulfill the irrigation water demand. Consequently, harvest failure often occurs in various locations during the Cultivation Season II. Therefore, a study on the optimization of efficient water utilization of Setupatok reservoir for irrigation purposes is required. The optimum water utilization capability of Setupatok Reservoir can be obtained by using the Linier Program for water utilization analysis, which is combined with the operational simulation technique of reservoir water release setting. The optimum capability of the reservoir water utilization was measured based on the achievement of annual Cultivation Intensity by considering the ratio of real release and targeted water demand (factor k) and the reliability of the reservoir operation. The simulation of the reservoir operation was calculated based on the water availability data in 10 years or between 2002 and 2011. It included 12 scenarios with variations of the beginning of the cultivation pattern, which was from November, December or January. The pattern used was the same as the existing pattern: rice/cane-rice/cane-palawija/cane. The proposed cultivation pattern was rice/cane-rice/palawija/cane-palawija/cane. Water balance analysis at the existing condition for rice/caneârice/caneâ palawija/cane pattern with Cultivation Intensity (IT) of 247% indicated that the ratio of water availability and water demand was 0.72 within reservoir reliability of 58.33%. This study showed that the best results would be achieved by the proposed pattern, which was rice/caneârice/palawija/caneâpalawija/cane with the beginning of cane cultivation in December and carried out in 2 (two) rotation water supply. The IT value was 258% that resulted factor k and reservoir reliability of 0.98 and 97.86%, respectively.